DYEING OF SILK WITH LAWSONIA INERMIS[HENNA] EXTRACT AND STUDYON THEIR FASTNESS PROPERTIES - Ramasubramaniam; Anandhavel; P, Nataraj; Selvan, Tamil; Kumaran, Selva (International Journal of Research -GRANTHAALAYAH, 2016)
The main focus of the project was to dye the silk fabric using LawsoniaInermis dye (Henna). Dyeing of silk using henna would be possible using mordant. Potash Alum was chosen as the mordant because of its environment friendly nature. Four dyed samples were prepared as follows- sample dyed without mordant, sample dyed premordanted, sample dyed post mordanted, and simultaneous mordented. Better results were obtained when dye extraction was carried out in alkaline condition (pH 9) and dyeing in acidic medium (pH 5). Different hues were obtained on silk fabric samples from the same dye extract. Their fastness properties were studied and it was found that the simultaneous mordanted samples displayed a better fastness properties compared to the others.